The Impact of Centralized Quarantine on Mental Health of People Affected By Covid-19: A Systematic Review - Qathrin Nada; Saryono Saryono; Mekar Dwi Anggraeni (Universitas Aisyah Pringsewu, 2021)
Quarantine is known as one of the strategies to minimize the spread of Covid-19. This study aims to seek scientific evidence regarding the impact of centralized quarantine on the mental health of people affected by Covid-19. We conducted a systematic search for articles evaluating the mental health conditions of Covid-19 sufferers and suspected cases who were undergoing quarantine. The search for articles was carried out on December 31, 2020, through the Science Direct, PubMed, and Springer databases. Among 704 articles, only seven reviews met our criteria. One study evaluating the mental condition of quarantine Covid-19 patients in hospital compared to a non-quarantine control group found that patients experienced higher rates of depression, anxiety, and post-traumatic stress symptoms. Depression and anxiety were reported to be health problems experienced by participants in all studies. Factors related to mental health conditions, namely female gender, lower education level, lower-income, and married status. Social stressors in the form of negative stigma from the community, lack of adequate information, and poor quarantine facilities worsen mental health conditions. Centralized quarantine has negative consequences for the mental health of sufferers of Covid-19. More attention needs to be paid to the mental health well-being of patients undergoing in centralized quarantine. The right strategy to minimize the negative impact of quarantine needs to be implemented in order to achieve individual mental health and prevent long-term complications.